2023
DOI: 10.3390/en16031128
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Rheological Parameters of Non-Newtonian Fluids on an Example of Biogas Plant Substrates

Abstract: Non-Newtonian fluids are commonly used in a wide range of industries; one example are in biogas power plants. Proper measurements and modeling of such fluids can be crucial from the design and operations point of view. Results presented in this study covered seven samples from three plants (a sewage sludge treatment plant, utilization biogas station and a biogas plant in a sugar factory), including mechanically thickened excessive activated sludge (MTEAS), sugar beet pulp (SBP), liquid fruit and vegetable wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Samples of digested pulp or composted material intended for typical physical and chemical analyses should be rapidly cooled using existing methodologies, delivered to the laboratory, and placed in a refrigerator at temperatures between 0-4 • C. This is performed to halt biological activity and any biochemical processes [83]. Bacteria influence the rheological parameters of fluid without altering its structure from homogenous to heterogeneous [84][85][86]. However, in the developed methodology described in the study, maintaining the parameters of the collected digested pulp is crucial, as it is assumed that there is an effect of bacterial activity on its rheological properties.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Samples of digested pulp or composted material intended for typical physical and chemical analyses should be rapidly cooled using existing methodologies, delivered to the laboratory, and placed in a refrigerator at temperatures between 0-4 • C. This is performed to halt biological activity and any biochemical processes [83]. Bacteria influence the rheological parameters of fluid without altering its structure from homogenous to heterogeneous [84][85][86]. However, in the developed methodology described in the study, maintaining the parameters of the collected digested pulp is crucial, as it is assumed that there is an effect of bacterial activity on its rheological properties.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This suggests that the latter system exhibits a flow pattern closer to the equilibrium. For predictive estimates of the rheological behavior of pseudoplastic and viscous plastic systems, the various empirical models of Herschel-Buckley, Ostwald-de Wael, and Casson [35,51,53] are taken into account, after which experimental data were approximated in the "load" mode in the range of shear rates 7-1080 s −1 .…”
Section: Rheological Behaviour Of Hydrogel Suspensionsmentioning
confidence: 99%
“…A survey of the available literature clearly indicates that substrate origin and properties, represented by interaction 1 in Figure , play a central role in the regulation of CSTBR rheology (Table ). This aspect was addressed by studies involving different AD applications with a variety of substrate types ,,,, or studies that evaluated the effect of pretreatments on substrate properties and sludge rheology. , Our own studies of rheological characterization of sludge from 33 different reactors indicated that the rheological fluid properties and process parameters, including TS or TVS contents, correlate best among reactors digesting the same substrate type, but cannot be extrapolated broadly across a range of substrate profiles and operational conditions. , Similarly, Jankowska et al reported that different substrate mixtures have vastly different rheological properties, even at the same solid contents. To systematically assess the effects of different substrate components on digestate rheology, Miryahyaei et al evaluated how rheological behavior of sewage sludge changes upon codigestion with cellulose, proteins, or lipids.…”
Section: Rheology Regulation In Admentioning
confidence: 99%
“…A survey of the available literature clearly indicates that substrate origin and properties, represented by interaction 1 in Figure 1, play a central role in the regulation of CSTBR rheology (Table 1). This aspect was addressed by studies involving different AD applications with a variety of substrate types 21,22,42,50,70 or studies that evaluated the effect of pretreatments on substrate properties and sludge rheology. 51,52 Our own studies of rheological characterization of sludge from 33 different reactors indicated that the rheological fluid properties and process parameters, including TS or TVS contents, correlate best among reactors digesting the same substrate type, but cannot be extrapolated broadly across a range of substrate profiles and operational conditions.…”
Section: ■ Rheology Regulation In Admentioning
confidence: 99%
See 1 more Smart Citation